Cover Image. (11th March 2021) - Crabot, Julie; Polášek, Marek; Launay, Bertrand; Pařil, Petr; Datry, Thibault
Abstract : The cover image is based on the Original Article Drying in newly intermittent rivers leads to higher variability of invertebrate communities, by Julie Crabot et al., https://doi.org/10.1111/fwb.13673 .